2020
DOI: 10.1001/jamanetworkopen.2020.24661
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Prepregnancy Body Mass Index With Fetal Growth and Neonatal Thalamic Brain Connectivity Among Adolescent and Young Women

Abstract: Key Points Question Is maternal prepregnancy body mass index among adolescent and young women associated with fetal growth and neonatal functional connectivity? Findings In this cohort study that included 129 pregnant adolescent and young adult women, maternal prepregnancy body mass index had a significant positive association with the slope of estimated fetal weight and with greater local thalamic and lower frontothalamic connectivity. Meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 53 publications
1
34
0
3
Order By: Relevance
“…This indicated that pre-pregnancy weight might influence longevity in the offspring. Furthermore, recent findings suggest that pre-pregnancy BMI is associated with the development of regulation of body weight and thalamic functional brain connectivity in the offspring [ 20 ]. Pre-pregnancy BMI may be one of the most important modifiable environmental factors that may dictate the life expectancy of and brain development in newborns, and their later health status and risk of chronic diseases [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that pre-pregnancy weight might influence longevity in the offspring. Furthermore, recent findings suggest that pre-pregnancy BMI is associated with the development of regulation of body weight and thalamic functional brain connectivity in the offspring [ 20 ]. Pre-pregnancy BMI may be one of the most important modifiable environmental factors that may dictate the life expectancy of and brain development in newborns, and their later health status and risk of chronic diseases [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sample sizes and ages at scan are shown in Supplementary Table 1 . Fifty-two studies were completely cross-sectional and performed only one scan per each subject ( Hazlett et al, 2012 ; Deniz Can et al, 2013 ; Deoni et al, 2013 , 2015 ; Gao et al, 2013 ; O’Muircheartaigh et al, 2013 , 2014 ; Qiu et al, 2013a , 2015b ; Broekman et al, 2014 ; Dean et al, 2014b , c , 2017 , 2018a , b ; Grewen et al, 2014 ; Travis et al, 2014 ; Zhang et al, 2014 ; Donald et al, 2015 ; Langer et al, 2015 ; Ou et al, 2015 ; Poh et al, 2015 ; Spann et al, 2015a , b , 2020a , b ; Ferradal et al, 2016 , 2019 ; Li et al, 2016 ; Sethna et al, 2016 ; Adibpour et al, 2018 , 2020 ; Lugo-Candelas et al, 2018 ; Monnelly et al, 2018 ; Chen et al, 2019 ; Hernandez-Castillo et al, 2019 ; Lebenberg et al, 2019 ; Lehtola et al, 2019 ; Ong et al, 2019 ; Tuulari et al, 2019 ; Acosta et al, 2020a , b , 2021 ; Alexander et al, 2020 ; Bruchhage et al, 2020 ; Camacho et al, 2020 ; Dowe et al, 2020 ; Fenchel et al, 2020 ; Gale-Grant et al, 2020 ; Graham et al, 2020 ; Merhar et al, 2020 ; Merz et al, 2020 ). The remaining studies ( n = 34) were longitudinal and conducted serial scans on the same individuals ( Geng et al, 2012 , 2016 ; ...…”
Section: Resultsmentioning
confidence: 99%
“…Serial scans included two to seven scans per subject, most typically three scans per subject. The majority of the studies ( n = 70) used 3 Tesla MRI scanners ( Geng et al, 2012 , 2016 ; Hazlett et al, 2012 ; Deoni et al, 2013 , 2015 ; Gao et al, 2013 , 2014a , b ; Li et al, 2013 , 2014a , b , c , 2015a , b ; Sadeghi et al, 2013 ; Alcauter et al, 2014 , 2015 ; Bompard et al, 2014 ; Chen et al, 2014 , 2019 ; Dean et al, 2014a , b , c , 2015a , b , 2017 , 2018a , b ; Grewen et al, 2014 ; Zhang et al, 2014 ; Donald et al, 2015 ; Langer et al, 2015 ; Spann et al, 2015a , b , 2020a , b ; Swanson et al, 2015 ; Chang et al, 2016 ; Croteau-Chonka et al, 2016 ; Ferradal et al, 2016 , 2019 ; Kim et al, 2016 ; Meng et al, 2017 ; Adibpour et al, 2018 , 2020 ; Lugo-Candelas et al, 2018 ; Monnelly et al, 2018 ; Ahn et al, 2019 ; Dai et al, 2019a , b ; Hernandez-Castillo et al, 2019 ; Hu et al, 2019 ; Lebenberg et al, 2019 ; Lehtola et al, 2019 ; Tuulari et al, 2019 ; Wang et al, 2019 , 2012 ; Acosta et al, 2020a , b , 2021 …”
Section: Resultsmentioning
confidence: 99%
“…Prior investigations into maternal obesity and overweight during pregnancy related infant neurodevelopment have revealed widespread functional connectivity and white matter tract alterations in the neonate brain [22][23][24][25] . Similarly, a recent study found that higher pre-pregnancy maternal BMI during gestation associated with variations in functional connectivity in fetal prefrontal, frontal and insular brain regions 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The delicate developmental and recon guration processes in brain functional networks during gestation and the rst years, respectively, present a time window in brain development, that has been shown to be particularly vulnerable for disruption by endogenous and exogenous factors 13 . Prior human MRI neonate studies focusing on obese and overweight pregnancies have revealed that maternal adiposity is associated with widespread alterations in the anterior brain white matter tract integrity 22 and in functional networks 23,24 with emphasis on sensory cue and reward processing, cognitive and motor control in the neonate brain 25 .…”
Section: Introductionmentioning
confidence: 99%